1992
DOI: 10.1111/j.1467-9450.1992.tb00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Time perception: Effects of sex and sound intensity on scales of subjective duration

Abstract: Six women and six men reproduced ten time intervals varying in logarithmic steps between 1.3 and 20 s. The durations were indicated by white noise of 10, 25, 40 and 55 dB SL, different sound intensities in different sessions. It was found that (i) greater sound intensity entails shorter reproductions, and (ii) reproductions by male observers are shorter than those by female, although for both (i) and (ii) there is an interaction with the standard durations. The data were treated in accordance with the "paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 19 publications
5
32
0
3
Order By: Relevance
“…According to Hancock (1999), the gender difference in time estimation might be attributed to different spatio-temporal perceptual capabilities. Our results support the findings of many other researchers who have found that gender differences exist in short-time perception (Delay and Richardson 1981;Rammsayer and Lustnauer 1989;Eisler and Eisler 1992;Hancock et al 1992).…”
Section: Gendersupporting
confidence: 96%
“…According to Hancock (1999), the gender difference in time estimation might be attributed to different spatio-temporal perceptual capabilities. Our results support the findings of many other researchers who have found that gender differences exist in short-time perception (Delay and Richardson 1981;Rammsayer and Lustnauer 1989;Eisler and Eisler 1992;Hancock et al 1992).…”
Section: Gendersupporting
confidence: 96%
“…Beginning in the late 1980s and early 1990s, some researchers again considered the issue. Some found a sex difference that seemed to echo what was revealed in early research (H. Eisler & A. D. Eisler, 1992;Hancock, Arthur, Chrysler, & Lee, 1994;Hancock, Vercruyssen, & Rodenburg, 1992). Others thought that the literature showed that females underestimate durations more than do males (Kellaris & Mantel, 1994).…”
Section: Sex Differences In Psychological Timementioning
confidence: 71%
“…D. Eisler, 1995;H. Eisler & A. D. Eisler, 1992) contained data on sex differences in the slope of the psychophysical function relating subjective to objective duration.…”
Section: Psychophysical Slopementioning
confidence: 99%
“…Perhaps one encouraging fact is that despite the aversion of the use of a counting strategy by subjects in psychophysical studies of time estimation (note the request not to count off time in a number of studies; e.g., Eisler & Eisler, 1992), counting does improve accuracy of the time estimation (Fetterman & Killeen, 1990). Conceivably, counting would be a cognitive strategy that is arousal-dependent (Frankenhaeuser, 1959), but also attention-focusing, and could serve the (theoretically) useful purpose of coordinating between the pacemaker notion of a cognitive-timer and that of an attention-dependent counting of subjective time units.…”
Section: The Cognitive-timer Modelmentioning
confidence: 97%